Infrastructural and Regulatory Bottlenecks of Intensification and Diversification of Regional Agricultural Trade and Value Addition in Tanzania - Yade, Sambane; Tadesse, Getaw (International Water Management Institute, 2023)
The purpose of this brief is to identify and summarize the critical bottlenecks related to the policy and regulatory environment, infrastructure, and public services that constrain the intensification and diversification of Tanzania’s intra-regional trade and value addition. Unlike Africa’s trade with the rest of the world, which mainly consists of primary commodities, intra-regional agricultural trade in the continent is heavily dominated by processed products. Most of the bottlenecks limiting the expansion of intra-regional trade are associated with intermediary actors involved in agri-food processing, transportation and wholesale and retail trade. However, before exploring these bottlenecks, we outline Tanzania’s trade potential, competitiveness, and priority value chains.